2015
DOI: 10.1016/j.ajpath.2015.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Homozygosity and Heterozygosity for Null Col5a2 Alleles Produce Embryonic Lethality and a Novel Classic Ehlers-Danlos Syndrome–Related Phenotype

Abstract: Null alleles for the COL5A1 gene and missense mutations for COL5A1 or the COL5A2 gene underlie cases of classic Ehlers-Danlos syndrome, characterized by fragile, hyperextensible skin and hypermobile joints. However, no classic Ehlers-Danlos syndrome case has yet been associated with COL5A2 null alleles, and phenotypes that might result from such alleles are unknown. We describe mice with null alleles for the Col5a2. Col5a2 À/À homozygosity is embryonic lethal at approximately 12 days post conception. Unlike pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 30 publications
(52 reference statements)
1
32
2
Order By: Relevance
“…Unlike heterozygous Col5a1 þ/À adult mice, which exhibit hyperextensible skin at both high and low stress, and on electron microscopic examination display large-diameter dermal aggregates of collagen fibrils with cauliflower-like contours, 14 cardinal features of cEDS, 12 adult heterozygous Col5a2 þ/À mice exhibited hyperextensible skin at high, but not low, stress and dermal collagen fibrils with relatively mild abnormalities in contour and diameter. 16 Together, these data suggested that human COL5A2 þ/À heterozygotes, although likely more susceptible to skin tearing/wounding than normal, might not present with frank cEDS. This conclusion, together with the finding that aortas of Col5a2 þ/À heterozygous mice have reduced tensile strength and increased elasticity, raised the question of the clinical ramifications of the COL5A2 þ/À genotype in human populations.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…Unlike heterozygous Col5a1 þ/À adult mice, which exhibit hyperextensible skin at both high and low stress, and on electron microscopic examination display large-diameter dermal aggregates of collagen fibrils with cauliflower-like contours, 14 cardinal features of cEDS, 12 adult heterozygous Col5a2 þ/À mice exhibited hyperextensible skin at high, but not low, stress and dermal collagen fibrils with relatively mild abnormalities in contour and diameter. 16 Together, these data suggested that human COL5A2 þ/À heterozygotes, although likely more susceptible to skin tearing/wounding than normal, might not present with frank cEDS. This conclusion, together with the finding that aortas of Col5a2 þ/À heterozygous mice have reduced tensile strength and increased elasticity, raised the question of the clinical ramifications of the COL5A2 þ/À genotype in human populations.…”
mentioning
confidence: 86%
“…12 To determine in vivo effects of reduced or absent a2(V) chains, we recently generated and characterized mice with constitutively null Col5a2 alleles. 16 Homozygosity for the null Col5a2 allele yielded embryonic lethality at approximately 12 days after conception, 16 approximately 2 days later than the embryonic lethality previously described for homozygous null Col5a1 À/À mice, 11 although embryos of both genotypes had similar cardiovascular signs, suggesting deficits in early cardiovascular integrity. However, although Col5a1 À/À embryos lacked identifiable mesenchymal collagen fibrils, 11 Col5a2 À/À embryos had identifiable mesenchymal collagen fibrils, albeit with abnormally large diameters and abnormal configurations.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Embryonic lethality at E10-E12 (Wenstrup et al, 2004;Park et al, 2015) VI (G) Bethlem myopathy 1 (Scacheri et al, 2002;Pepe et al, 1999;Pan et al, 1998;Lucioli et al, 2005;Lampe et al, 2005;Jöbsis et al, 1996;Baker et al, 2007) (G) Ullrich congenital muscular dystrophy 1 (Lampe et al, 2005;Kawahara et al, 2007;Giusti et al, 2005;Baker et al, 2005) Dystonia 27 (Zech et al, 2015) Abnormalities in morphology of l muscle, impaired skeletal muscle contractility, myopathy (Bonaldo et al, 1998) VII (G) Epidermolysis bullosa dystrophica, multiple types (Shinkuma, 2015;Fine et al, 1989;Christiano et al, 1993Christiano et al, , 1994Christiano et al, , 1995Christiano et al, , 1996Woodley et al, 2004) Postnatal lethality within the first week from complications of blistering (Heinonen et al, 1999) VIII (N) Corneal dystrophies (Biswas et al, 2001) Dysgenesis of the anterior segment of the eye (Hopfer et al, 2005) IX (G) Multiple epiphyseal dysplasia 2, 3 and 6 (Paassilta et al, 1999;Jeong et al, 2014;Holden et al, 1999;Czarny-Ratajczak et al, 2001) Stickler Syndrome 4 and 5 (Van Camp et al, 2006;Baker et al, 2011) (N) Intervertebral disc disease (Paassilta et al, 2001;Annunen et al, 1999b) one, two or all three distinct chains of the triple helix in different combinations to directly bind a molecule ( Fig. 2B; modes 1-3).…”
Section: (G)mentioning
confidence: 99%